[PP.35.07]: HAEMOSTATIC BENEFITS OF DUAL RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM BLOCKADE. (June 2015) - Gromotowicz-Poplawska>, A.>; Kramkowski, K.; Mikita, J.; Strzyz, M.; Kisiel, W.; Szemraj, J.; Chabielska, E.
Abstract : Objective: The clinical studies indicate that co-administration of aldosterone receptor blocker with standard therapy reduces mortality in patients with heart failure. We confirmed previously a strong prothrombotic effect of aldosterone and angiotensin II in the experimental models of thrombosis. Therefore, we suggest that the additional benefits of dual renin-angiotensin-aldosterone system (RAAS) blockade may be related to the effects of drugs on haemostasis. The aim of the present study was to investigate the effect of combined spironolactone (SPIRO) and quinapril (QUIN) administration on haemostasis in hypertensive rats. Design and method: Wistar 2K1C-hypertensive rats were used (n = 10–12). SPIRO (20 mg/kg), QUIN (3 mg/kg), or VEH (gummi arabici, 5% aq.sol.) were administered p.o. for 10 days. Systolic blood pressure was measured. The venous thrombosis was induced by the vena cava ligation on the 11th day. The formed thrombus was removed and weighted. The effect of drugs on platelets adhesion to collagen (ex vivo and in vitro), bleeding time (BT) and amidolytic activity of thrombin was evaluated. Tissue plasminogen activator (t-PA), plasminogen activator inhibitor type-1 (PAI-1), tissue factor (TF) and thrombin-activatable fibrinolysis inhibitor (TAFI) plasma levels were measured by ELISA. The plasma levels of some oxidative stress markers (H2O2, MDA) were measured. Results: SPIRO and QUIN reduced TF, PAI-1, TAFI plasma level (p < 0.001 vs VEH), while effects of QUIN were stronger (p < 0.001 vs SPIRO) and the most pronounced changes were observed after drugs co-administration. SPIRO/QUIN markedly reduced H2O2 and MDA plasma levels, but the strongest effect was observed after combined treatment. SPIRO/QUIN (ex vivo) or their metabolites (in vitro) reduced platelets adhesion to collagen. Only dual RAAS blockade significantly reduced thrombus weight and diminished thrombosis incidences. Conclusions: The most pronounced changes in haemostasis, leading to marked reduction of venous thrombosis, were obtained after combined SPIRO and QUIN administration. The mechanism was related to inhibition of coagulation, fibrinolysis augmentation, platelets adhesion reduction and oxidative stress impairment. This study indicates that additional benefits of dual RAAS blockade observed clinically may be also a result of drugs effect on haemostatic balance restoration.